1992
DOI: 10.1111/j.1360-0443.1992.tb01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous drug use and HIV transmission amongst inmates in Scottish prisons

Abstract: The intravenous drug use behaviour and HIV risk reduction strategies used by a group of Scottish inmates prior to prison, during imprisonment and as expected after release was investigated. From a sample of 559 inmates (480 males and 79 females) 27.5% were involved in IVDU prior to imprisonment, 7.7% on at least one occasion during a period of imprisonment and 14.7% expected to do so after release. Prior to imprisonment 17.3% had shared needles, 5.7% at some time during imprisonment and 4.3% expected to do so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 6 publications
1
30
0
3
Order By: Relevance
“…Some have suggested that the majority of HCV infections among IDUs occur outside prison [24,25] and that HCV transmission in prison is uncommon [10][11][12]. The reason for the difference in HCV incidence is that those studies recruited prisoners without specific risk factors.…”
Section: Discussionmentioning
confidence: 97%
“…Some have suggested that the majority of HCV infections among IDUs occur outside prison [24,25] and that HCV transmission in prison is uncommon [10][11][12]. The reason for the difference in HCV incidence is that those studies recruited prisoners without specific risk factors.…”
Section: Discussionmentioning
confidence: 97%
“…Prisons contain a sizeable sample of marginalized people, and they can readily be approached in research projects [2]. Prison populations have an overrepresentation of problematic alcohol and drug users [8][9][10][11][12][13]. A meta-analysis of surveys T. Lintonen (&) Á Y. Obstbaum Finnish Foundation for Alcohol Studies, Helsinki, Finland e-mail: tomi.lintonen@uta.fi on alcohol and drug use in prison in Anglo-Saxon countries shows that different surveys tend to yield highly variable estimates on substance abuse and dependence in prisons, but any estimate is typically much higher than in the general population [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition to the high prevalence of HIV among recent admitted individuals, it is wellknown that in some prisons risk behavior for HIV infection can be very high. 14,16 A number of studies conducted in the United States and elsewhere have found that a substantial proportion of prisoners engage in highrisk sexual activity and/or intravenous drug use while in prison. 14,16,17 In a recent Scottish study 5 it was demonstrated that 27% of the inmates reported injecting drug usage any time in life.…”
Section: Introductionmentioning
confidence: 99%